DAMPAK DEPRESI ANTENATAL TERHADAP HASIL KELAHIRAN: SYSTEMATIC REVIEW - Restu Apriena Putri; Tris Eryando (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
The Effect of Antenatal Depression to Birth Outcomes: A Systematic ReviewBackground: Mental health problems is an important public health challenge. There are 10% of pregnant women with mental disorders, especially depression. Depression affects adverse birth outcomes such as premature birth, low birth weight, low APGAR score, small head circumference and small for gestational (SGA). Objective: The purpose of this study is to determine the effect of antenatal depression on birth outcomes. Method: This study use a systematic review method using PRISMA-P (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocole) 2009. Results: From 836 documents, 5 studies were selected from Vietnam, Pakistan, Malaysia, The United States and Australia. 4 studies is a prospective cohort study design and 1 cross sectional study showing the negative effects of antenatal depression on birth outcomes. Conclusion: Antenatal depression has a negative impact on birth outcomes by increasing the risk of preterm birth (<37 weeks), increasing the risk of LBW birth (2500 grams), increasing the risk of a low APGAR score, and increasing the risk of having a small for gestational (SGA) baby.